Synthesis of Aminoalkyl-Functionalized 4-Arylquinolines from 2-(3,4-Dihydroisoquinolin-1-yl)anilines via the Friedländer Reaction - Rozhkova, Yuliya S.; Storozheva, Tatyana S.; Plekhanova, Irina V.; Gorbunov, Alexey A.; Smolyak, Andrej A.; Shklyaev, Yurii V. (Synthesis, 2021)
A new approach for the efficient and convenient synthesis of novel aminoalkyl-functionalized 4-arylquinolines via the Friedländer reaction of differently substituted 2-(3,4-dihydroisoquinolin-1-yl)anilines with various α-methylene ketones in acetic acid was developed. The reaction allows easy access to a diversity of 4-arylquinoline derivatives in moderate to excellent yields under mild conditions.
Keywords: Friedländer reaction; Schiff bases; 2-(3,4-dihydroisoquinolin-1-yl)anilines; ketones; acetic acid; 4-arylquinolines